Moving Forward by Stimulating the Brain: Transcranial Direct Current Stimulation in Post-Stroke Hemiparesis - Peters, Heather T.; Edwards, Dylan J.; Wortman-Jutt, Susan; Page, Stephen J. (Frontiers in Human Neuroscience, 2016)
Stroke remains a leading cause of disability worldwide, with a majority of survivors experiencing long term decrements in motor function that severely undermine quality of life. While many treatment approaches and adjunctive strategies exist to remediate motor impairment, many are only efficacious or feasible for survivors with active hand and wrist function, a population who constitute only a minority of stroke survivors. Transcranial direct current stimulation (tDCS), a type of non-invasive brain stimulation, has been increasingly utilized to increase motor function following stroke as it is able to be used with stroke survivors of varying impairment levels, is portable, is relatively inexpensive and has few side effects and contraindications. Accordingly, in recent years the number of studies investigating its efficacy when utilized as an adjunct to motor rehabilitation regimens has drastically increased. While many of these trials have reported positive and promising efficacy, methodologies vary greatly between studies, including differences in stimulation parameters, outcome measures and the nature of physical practice. As such, an urgent need remains, centering on the need to investigate these methodological differences and synthesize the most current evidence surrounding the application of tDCS for post-stroke motor rehabilitation. Accordingly, the purpose of this paper is to provide a detailed overview of the most recent tDCS literature (published 2014-2015), while highlighting these variations in methodological approach, as well to elucidate the mechanisms associated with tDCS and post-stroke motor re-learning and neuroplasticity.